Changes in nutritional quality-related traits of quinoa seeds under different storage conditions - Granado-Rodríguez, Sara; Maestro-Gaitán, Isaac; Matías, Javier; Rodríguez, María José; Calvo, Patricia; Hernández, Luis Eduardo; Bolaños, Luis; Reguera, Maria (Frontiers in Nutrition, 2022)
Within the context of climate change and its impact on global food security, seed storage has become key, as it ensures long-term food and next-season seed preservation. Aiming at evaluating quality-related changes in quinoa seeds over storage time, different storage temperatures (−20℃, 4℃, 12℃, 25℃, and 37℃) and humidity conditions (use of silica gel or not) were studied and different seed nutritional parameters were evaluated at different points during a year of storage. Also, to determine if these variations could be conditioned by the genotype used, two quinoa cultivars were compared. The results proved that quinoa seed quality is highly dependent on the storage temperature but is not consistently affected by the use of silica gel if the seed moisture content (SMC) is kept between 5% and 12%. Furthermore, quality can be maintained and even improved by keeping SMC lower than 12% and storage temperatures low (4°C). Under these conditions (at 4°C in hermetic packaging with or without silica gel), and after 12 months of storage, there was an increase in amino acids like isoleucine, serine, arginine, glycine, and glutamic acid and in seed viability and germination. On the contrary, quinoa seeds stored at 37°C showed an accumulation of reactive oxygen species (ROS) which was related to a lower antioxidant capacity and a reduction in the contents of essential amino acids like isoleucine, lysine, histidine, and threonine, resulting in a delayed and reduced germination capacity, and, therefore, lower seed quality. Besides, quality-related differences appeared between cultivars highlighting differences linked to the genotype. Overall, this work demonstrates that optimal storage temperatures and SMC can preserve or even improve quinoa seed nutritional quality, which in turn can impact food safety and agriculture.